Teaching SE principles : combining inductive instruction and discussion tools - Moura, Isabel Cristina A. A. (2010)
This research explores the effect on students’ achievements of integrating inductive instruction (i.e., project and other forms of active learning) and the use of a forum tool in a web-based Software Engineering (SE) introductory course. Using two different editions of the same course, the study portrays the changes in it from the absence (in the 2008 edition) to the presence (in the 2009 edition) of directives to use an online forum for reusing students’ contributions “as resource for further learning”. About 80 undergraduate students participated in the study. Data sources included students’ practices, individual and team contributions to the forum, and perceptions of using the discussion tool to learn SE principles. Although students tended mostly to read rather than post entries to the forum, this exploratory study shows how the above referred integration had a positive influence on students’ achievements, making them rise. Implications for the classroom are discussed.